Correlation between cultural dimensions and their influence on conflict style preferences - Rachwal-Mueller, A.; Рахвал-Мюллер, А. (Харківський національний автомобільно-дорожній університет, 2023)
This paper offers a multifaceted exploration of the intricate interplay between cultural dimensions and preferences in conflict resolution styles. It delves into the profound influence of cultural values on the choices individuals make when managing conflicts, enhancing our understanding of this complex relationship. Defining culture and conflict as central constructs, the paper investigates several key cultural dimensions within Hofstede's framework. It focuses on individualism and collectivism, high and low power distance, and high and low uncertainty avoidance. Few studies cover the research on power distance and conflict style preference, underscoring the importance of understanding how individuals choose styles that align with their cultural norms, whether maintaining low or high power distance within their own cultures. The study uncovers the correlation between different cultural types and conflict management styles. In cases of individualism, there is a preference for an avoidance style of conflict management, while collectivist cultures typically lean towards compromising and obliging conflict styles. In situations marked by high power distance, members of high power cultures are more likely to adopt an avoidance conflict style. The research holds significance for managing intercultural conflicts across various contexts, particularly in the realms of global governance, international relations, and multicultural team management. The findings provide a valuable reference for managers striving to navigate intercultural tensions and promote effective conflict resolution strategies aligned with cultural values. While this study offers valuable insights, it highlights the need for further in-depth research on additional cultural dimensions. This paper contributes to understanding the intricate relationship between culture and conflict resolution. It serves as a guide for analyzing preferences in intercultural conflicts, promoting conflict resolution management in multicultural projects, and advancing cross-cultural cooperation and understanding. Continuous research in this field is essential for more effective conflict management in an increasingly diverse global landscape.
Взаємозв'язок між культурними вимірами та їх вплив на вибір стилів вирішення конфліктів
Keywords: cultural dimensions; intercultural communication; conflict style preferences; conflict management; intercultural conflict resolution; international relations; cross-cultural cooperation; культурні виміри; міжкультурна комунікація; вибір стилів вирішення конфліктів; управління конфліктами; міжкультурне вирішення конфліктів; міжнародні відносини; міжкультурне співробітництво; 303.7:316.72:659.22; 10.30977/ЕТК.2225-2304.2023.42.121